Development of a measurement and feedback training tool for the arm strokes of high-performance luge athletes - Lembert, S.; Schachner, O.; Raschner, C. (Journal of Sports Sciences, 2011)
Previous studies have shown that the start plays a critical role in sliding events and explains more than 55% of the variance of the final time in luge. Experts evaluate the contribution of the arm strokes to be 23% of the total starting performance. The aim of the present study was to develop a measurement and feedback training tool (Speedpaddler) for the arm strokes of high-performance luge athletes. The construction is an aluminium alloy framework with a customary belt conveyor system, which is driven by two synchronized servo motors. Training is possible with constant speeds up to 12 m/s or several speed curves, which simulate the acceleration of different luge tracks. The construction facilitates variations in the inclination and speed of the conveyor belts and thereby the resistance and movement speed. If the athlete accelerates the conveyor belts during arm-paddling, the torque of the motors decreases. Torque measurements and high-speed video offer valuable insights into the several technique criteria. Comparisons of arm-paddle cycle durations on ice and on the Speedpaddler with 18 luge athletes (national team and juniors) showed no statistical differences. The Speedpaddler might be a useful tool to improve starting performance all year round.